Penetapan Harga Makanan dan Minuman - Khoiriah, Misbahul; Harahap, Ikhwanuddin; Harahap, Risalan Basri (Jurnal El-Thawalib, 2021)
Setting a high price in a tourist place is something that is not foreign to today’s society, even people think it is a natural thing. But, something that is considered normal by the community is not necessarily justified by islam. Islam places great emphasis on the value of justice in every aspect of life. Therefore, it is natural if justice is realized through market activies which are something that occurs from the will of the seller and buyer through demand and supply on a consensual basis, mutual pleasure and do not oppress each other. Rasulullah SAW recommended that price fixing be carried out based on market activities. This study axamines how the pricing of food and beverages at the Air Bangis beach tourism object, Sungai Beremas district west pasaman regency is axamined and how is the view of muamalah fiqh on the pricing that occurs in this tourist attraction. This research uses field research and sourced primary and secondary data. Data collection techniques used are observation, interviews and documentation. The results of this study indicate that the pricing of food and beverages at the Air Bangis beach attraction, Sungai Beremas District, West Pasaman regency is determined based on the will of the seller and not based on market activity on the basis of supply and demand. Setting a price that too high is not justified because it’s not in accordance with the muamalah principles in Islam. Rasulullah SAW recommended that every trader run his businessfairly and honestly. In this thesis the author also suggerts that traders make a list of food prices so that buyer know in advance the price they wiil buy to avoid disappointment for buyers.